Thinking-Aloud About Stereotypical Mainstream and Opiate-Dependent Lifestyle Images - Andrew McLeod; Jane Ogden (SAGE Open, 2013)
Participants (6 male, 4 female) on a methadone maintenance program completed a Think-Aloud procedure while viewing two stereotypical picture sets depicting opiate-dependent and mainstream lifestyles. Discourse analysis indicated that participants used two different discourses: a stereotype-affirming defensive discourse , which involved affirming the negative and positive stereotypes regarding opiate-dependent and mainstream lifestyles, and a stereotype-refuting defensive discourse , which involved refuting negative opiate-dependent stereotypes while constructing mainstream lifestyles and members negatively. We argue that both discourses fit within a grander discourse concerning normalization with participants’ speech functioning to defend them from being negatively stereotyped by making them “normal” members of society.